Allegorical Narratives of the Vietnam War - Burns, Tom (ITINERÁRIOS – Revue de Littérature, 2008)
In this article, the allegorical narrative is examined as a type of extended metaphor in which one simultaneous or parallel narrative structure is maintained together with another, one less “visible” or literal than the other. Three American novels of the period of the Vietnam War are analyzed as examples of allegorical narratives: Asa Baber’s The Land of a Million Elephants (1971); Robert Stone’s Dog Soldiers (1967), and Norman Mailer’s Why Are We in Vietnam? (1967). The fi rst, in spite of its apparent allegory, is shown to be more of a generalized fantasy, in the mode of Kurt Vonnegut, Jr, on western imperialism in Southeast Asia, while the second and third novels are more successful in constructing more specifically historical and critical allegorical narratives. Keywords: Allegorical narratives. Vietnam War literature. War fiction.